Overview of Dental Caries Severity and Nutritional Status in Preschool Children in Jatinangor in September 2014 - Putri, Anggita Dwi; MA, Etty Sofia; Djais, Julistio T.B. (Althea Medical Journal, 2016)
Background: The prevalence of dental caries in Indonesia is still high. The pain caused by dental caries could interfere with childrenâs ability to eat and even their growth. This study aimed to discover the proportion of dental caries severity related to nutritional status in children aged 3â5 years.Methods: This descriptive study was carried out in 3 Pre-school Education Centers (Pendidikan Anak Usia Dini, PAUD) in the sub-district of Jatinangor in September 2014. Sixty four children were selected through cluster random sampling as samples. The degree of caries was measured by def-t index. Nutritional status was determined by anthropometric measurements, i.e. body weight (BW)/body height (BH) or body mass index (BMI)/Age index.Results: There were 59 (92%) children suffered from dental caries out of which 48 (75%) children was severe, 6 (9%) children was moderate, and 10 (16%) children was mild. Furthermore, 18 (28%) children were mildly undernourished and 46 (72%) were well-nourished. Out of all the children with severe dental caries, 16 (34%) children had mild undernourishment while out of all the children with moderate-mild dental caries, 2 (12%) children had mild undernourishment.Conclusions: Children aged 3-5 years in the sub-district of Jatinangor have a relatively severe dental caries even though their nutritional status are generally good. Mildly undernourished children largely come from the group with severe dental caries. [AMJ.2016;3(2):314â8]Â DOI:Â 10.15850/amj.v3n2.464